2014
DOI: 10.1590/0103-8478cr20131065
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade microbiológica de filés de tilápia do Nilo (Oreochromis niloticus) durante o armazenamento em gelo

Abstract: RESUMO O objetivo do presente trabalho foi avaliar o frescor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
5
0
3
Order By: Relevance
“…It is important to highlight that the analysis was carried out on fish after being captured, with no washing with sanitizer or direct contact with ice (only with the sterile sampling bags). Soares et al (2014) in their study of Nile Tilapia (Orechromis niloticus), from fish caught in cages, observed an absence of S. aureus in all simples.…”
Section: Resultsmentioning
confidence: 97%
“…It is important to highlight that the analysis was carried out on fish after being captured, with no washing with sanitizer or direct contact with ice (only with the sterile sampling bags). Soares et al (2014) in their study of Nile Tilapia (Orechromis niloticus), from fish caught in cages, observed an absence of S. aureus in all simples.…”
Section: Resultsmentioning
confidence: 97%
“…Fish is an essential source of protein and provides many health benefits; however, it is a very perishable product and possesses a tendency for rapid microbial spoilage [5,6]. It has been shown that fish can cause foodborne illnesses [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…When improper handling and storage occurs, the fish deteriorates rapidly, and its shelf life decreases. The high levels of microbiological contamination may pose a potential public health risk with the consumption of fish [6,13]. Hence, this study aimed to evaluate the microbiological quality of ice and fresh tilapia samples commercialized in the Federal District.…”
Section: Introductionmentioning
confidence: 99%
“…E coli foi detectada a partir do 4º dia de refrigeração do pescado com incremento em UFC, à medida que o tempo de manutenção do pescado em gelo aumentou. Resultado semelhante ao achado em filés congelados de tilápia (Orechromis niloticus) realizado por Soares et al (2014), indicando que esta característica de crescimento desta bactéria seja comum entre pescados comercializados após armazenamento em gelo.…”
Section: Análise Microbiológicaunclassified